Investigation of activated carbon derived from rice straw biomass for removal of phenol from aqueous solution - Thi Thu Hoai Pham (Vietnam Journal of Science, Technology and Engineering, 2023)
The rapidly developing of industry and population leads to various problems, such as an increase in the energy used and discharging of pollutants into the environment. Water pollution is a big issue in Vietnam as well as in the world. Therefore, finding the method for the treatment of water is urgent.This work investigated activated carbon derived from rice straw biomass (ACRS) for the adsorption of phenol. The surface morphology, surface functional group, and surface area of the ACRS were determined by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, and Brunauer-Emmett-Teller (BET) analysis, respectively. ACRS had a porous structure along with a larger surface area of 216.3 m2/g, which effectively enhanced the adsorption performance of phenol. The removal performance of phenol increased with increasing the contact time (10-60 min), then reached equilibrium at 90 min. The maximum adsorption capacity of phenol using ACRS was 128.4 mg/g and the adsorption behaviour of the pollutant fit well to the Langmuir and Freundlich isotherms. Experimental results revealed that adsorption by surface area, activated sites, pores, and complexation between functional groups of the adsorbent and phenol were major mechanisms.